Push, Pull, And Mooring Effects on Gen Z’s Switching Intention in TikTok Shop - Putri Shandy Nur Cahyani; Ralina Transistari (International Journal of Management Science and Information Technology, 2026)
This study investigates the influence of Push, Pull, and Mooring (PPM) effects on the switching intention of Generation Z users of TikTok Shop in Indonesia. The rapid growth of social commerce, combined with regulatory changes that temporarily halted TikTok Shop operations in October 2023, triggered behavioral shifts among users. Applying the PPM framework, this study analyzes the extent to which push factors (e.g., dissatisfaction, high perceived price), pull factors (e.g., attractiveness of alternatives), and mooring factors (e.g., switching costs, subjective norms) influence users’ intention to switch platforms. Data were collected via a survey of 146 TikTok Shop users aged 17–27 who had used the platform prior to its closure. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4.0. The results show that both push and pull effects significantly and positively influence switching intention, with the pull effect emerging as the dominant factor. However, mooring effects do not have a significant influence on switching intention and do not moderate the relationship between push/pull effects and switching intention. These findings offer insights into consumer behavior in social commerce and provide strategic implications for e-commerce platforms seeking to retain users in a competitive market.